Suramin is a novel competitive antagonist selective to α1β2γ2 GABAA over ρ1 GABAC receptors. (October 2018) - Luo, Hui; Wood, Kristofer; Shi, Fu-Dong; Gao, Fenfei; Chang, Yongchang
Abstract: GABAA and GABAC receptors are both GABA-gated chloride channels with distinct pharmacological properties, mainly in their sensitivity to bicuculline and gabazine. In this study, we found that suramin, a purinergic receptor antagonist, is a novel competitive antagonist selective to GABAA over GABAC receptors. Specifically, suramin antagonized the GABA-induced current and the spontaneous opening current of the wild type α1β2γ2 GABAA receptor with high-level expression in Xenopus oocytes. The antagonism was concentration dependent with an IC50 that varied depending on the concentration of GABA, and with the lowest IC50 of 0.43 μM when antagonizing the spontaneous current. Thus, its potency is slightly higher than bicuculline on the same GABAA receptor. Suramin also antagonized the mouse native brain GABA receptors micro-transplanted into the Xenopus oocytes with its potency depending on the GABA concentration. In addition, in the presence of two fixed concentrations of suramin, the GABA concentration response of the receptor was shifted to the right without reduction of the maximum current. Thus, our results are consistent with that suramin is a competitive antagonist for the α1β2γ2 GABAA receptor. Interestingly, the rank order of maximum allosteric inhibition (efficacy) of spontaneous current of the GABAA receptor by three competitive antagonists was suramin > bicuculline > gabazine, similar to the rank order of their molecular weight. In contrast, similar to bicuculline, suramin has much lower potency in antagonizing the GABA-induced current of the ρ1 GABAC receptor. In conclusion, we have identified a novel GABAA receptor competitive antagonist, which is selective to the α1β2γ2 over ρ1 GABA receptors. Highlights: Suramin antagonized the GABA-induced current of the α1β2γ2 GABAA receptor. The IC50 of suramin inhibition was GABA concentration-depended. Suramin shifted GABA concentration-response to right without reducing the maximum. Suramin had much lower potency on the wild type ρ1 GABA receptor.